DAMPAK KEBERADAAN KAMPUS ITERA TERHADAP KOMPONEN LINGKUNGAN (SOSIAL, EKONOMI DAN KESEHATAN) MASYARAKAT SETEMPAT - Fitralia Elyza (Yayasan Akrab Pekanbaru, 2018)
The study aims to determine the environmental impact caused by the construction of ITERA campus (Intitute Teknologi of Sumatera). The sample was taken by random sampling samples in Way Hui Village which is the closest object from ITERA campus, then analyzed from each questionnaire. The results showed that the negative impact of development by respondents most such as increased air pollution, congestion, and road damage. from the economic sector, respondents get new jobs to become motorcycle taxi drivers and start a business like renthouse. In terms of environmental health 33 respondents showed the results of 13 respondents rarely affected by disease and 8 people responded to other diseases such as itching and coughing, 6 people affected by cough disease in the last 3 months. Keywords: questionnaire, pollution, renthouse, diseases.